2008
DOI: 10.1074/jbc.m707436200
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoinositide Binding to the Substrate Regulates Susceptibility to Proteolysis by Calpain

Abstract: Calpain-mediated proteolysis regulates cytoskeletal dynamics and is altered during aging and the progression of numerous diseases or pathological conditions. Although several cytoskeletal proteins have been identified as substrates, how localized calpain activity is regulated and the mechanisms controlling substrate recognition are not clear. In this study, we report that phosphoinositide binding regulates the susceptibility of the cytoskeletal adhesion protein ␣-actinin to proteolysis by calpains 1 and 2. At … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 49 publications
1
39
0
Order By: Relevance
“…In these hearts, which represent a basal state (as opposed to the stressed mdx in the previous experiment) of the GRMD heart at 25 months, levels of l-calpain were relatively unchanged; in contrast, content of m-calpain, a predominantly peripheral protease, were strongly reduced with treatment ( Figure 7B). Unchanged content of the sarcomeric protein cTnI coincident with reduced cleavage products of the structural/peripheral proteins a-spectrin (150 kDa), a-actinin (80 kDa), integrin b1 (75 kDa), and dysferlin (80 kDa) [30][31][32][33] in the tadalafil-treated hearts corroborated the concept of lower levels and activity of peripheral m-calpain in these nonstimulated dystrophic hearts. We did not, however, note changes in PKG1a content or the phosphorylation status of GSK3b or ERK1/2, although a decrease in ANP and modest increases in endothelial and neuronal nitric oxide synthases were seen ( Figure S1A).…”
Section: Modulated Trpc6 and Protease Content In Tadalafil-treated Grsupporting
confidence: 59%
“…In these hearts, which represent a basal state (as opposed to the stressed mdx in the previous experiment) of the GRMD heart at 25 months, levels of l-calpain were relatively unchanged; in contrast, content of m-calpain, a predominantly peripheral protease, were strongly reduced with treatment ( Figure 7B). Unchanged content of the sarcomeric protein cTnI coincident with reduced cleavage products of the structural/peripheral proteins a-spectrin (150 kDa), a-actinin (80 kDa), integrin b1 (75 kDa), and dysferlin (80 kDa) [30][31][32][33] in the tadalafil-treated hearts corroborated the concept of lower levels and activity of peripheral m-calpain in these nonstimulated dystrophic hearts. We did not, however, note changes in PKG1a content or the phosphorylation status of GSK3b or ERK1/2, although a decrease in ANP and modest increases in endothelial and neuronal nitric oxide synthases were seen ( Figure S1A).…”
Section: Modulated Trpc6 and Protease Content In Tadalafil-treated Grsupporting
confidence: 59%
“…These data are supported by recent protease-sensitivity experiments, which demonstrated that PI(4,5)P 2 binding decreases the proteolysis of ␣-actinin, suggesting a role in stabilizing the structure of the protein. In contrast, PI(3,4,5)P 3 binding enhanced ␣-actinin proteolysis, indicating an increase in the flexibility of the protein (341). The in vivo importance of the interaction between ␣-actinin and PI(4,5)P 2 was demonstrated by studies on Xenopus oocytes and hippocampal neurons, where decrease in the PI(4,5)P 2 concentration or inactivation of the PI(4,5)P 2 -binding site of ␣-actinin lead to the detachement of ␣-actinin from the plasma membrane and subsequent inhibition of the NMDA receptor activity (247).…”
Section: ␣-Actininmentioning
confidence: 94%
“…Second, it could adjust this force transmission through mechanisms such as the regulation of its integrin binding (56) or actin cross-linking (57) by phosphoinositides. Third, α-actinin could promote adhesion dynamics and force release by serving as a docking platform for FAK (44,58,59) or upon cleavage by calpain (60). Thus, although the specific mechanisms remain to be elucidated, these interactions could allow α-actinin to increase force generation through increased actin cross-linking and integrin binding.…”
Section: Discussionmentioning
confidence: 99%